State-empowered entities as sites of progress for international anti-trafficking law and policy? - Kane, Gillian (Frontiers in Human Dynamics, 2023)
Since the adoption of the Palermo Protocol in 2000, international anti-trafficking law and policy has developed significantly. While both States and non-state actors have had a role to play in such development, this article focuses on the contribution of what Sivakumaran (2017) labels as ‘state-empowered entities’ (SEEs), actors that are ‘empowered’ by states’ and thus cannot be seen as ‘truly non-state in character’. Indeed, a range of SEEs, such as UNODC, the Council of Europe’s Group of Experts on Action against Trafficking in Persons to name a few- engage substantively with international anti-trafficking law. Situated within a theoretical framework that views ‘soft’ law as fulfilling ‘a variety of legal and para-legal functions to reinforce and supplement hard law’ (Chetail, 2018), this article analyses the ongoing role of SEEs in operationalising international anti-trafficking law, highlighting the norm creation, interpretation, and enforcement functions that such entities can and do play. Ultimately, this article frames SEEs as underexplored sites of progress for international anti-trafficking law, and calls for more engagement with the work and output of relevant SEEs, within anti-trafficking research and practice.